Homoafetividade e abertura política em contos de Caio Fernando Abreu - Nascimento, Cyro Roberto de Melo (2014)
This text aims to study the literary representation of homoaffectivity in short stories of Caio Fernando Abreu in the context of brazilian redemocratization, specifically in the narratives published between 1982 and 1988. To understand the relation between literature and historical context in the tales, we betake, principally, to a notion of Literature and Society, as proposed for Antonio Candido. Relating the narratives of Caio Fernando Abreu with the military dictatorship and the redemocratization processes, as well as a generational project named contraculture, we aim to verify as the search for affection for men that desire others men may be conditioned for specific socio-hystorical conditions, understanding the literary work as a privileged field of representation and comprehension of reality